Prevalence of sports participation among Brazilian adolescents: a systematic review - Maillane-vanegas, Santiago [UNESP]; Codogno, Jamile Sanches [UNESP]; Turi, Bruna Camilo [UNESP]; Christofaro, Diego Giuliano Destro [UNESP]; Fernandes, Romulo Araújo [UNESP] (Universidade Federal de Santa Catarina, 2018)
The objective of this study was to describe the prevalence of sports participation in Brazilian children and adolescents using a systematic review approach. This review follows the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement and the protocol was previously registered on PROSPERO (95441), the searches were performed in the following electronic databases: PubMed, ScIELO, Bireme, and EMBASE. The search strategy included a combination of keywords: Children and adolescents, prevalence and sports participation. Four papers included 7104 adolescents aged from 10 to 18 years old, living in four different cities located at Southeast (n= 1) and South (n= 3) of Brazil data collections were carried out between 2004 and 2012. Most of the studies had cross-sectional design and the findings of all surveys were published in international journals. The definition of “sports participation” was not the same in all papers. The overall prevalence of sports participation among adolescents was 58.1%, higher among boys (65.9%) than in girls (51.5%). The systematic review identified that the prevalence of sports participation among Brazilian adolescents is low and significantly affected by gender.

O objetivo deste estudo foi descrever a prevalência da participação esportiva em crianças e adolescentes brasileiros por meio de uma revisão sistemática. Esta revisão segue os itens Preferred Reporting for Systematic reviews e Meta-Analysis (PRISMA) e o protocolo foi previamente cadastrado no PROSPERO (95441), as buscas foram realizadas nas seguintes bases de dados eletrônicas: PubMed, ScIELO, Bireme e EMBASE . A estratégia de busca incluiu uma combinação de palavras-chave: crianças e adolescentes, prevalência e participação esportiva. Quatro artigos incluíram 7104 adolescentes com idades entre 10 e 18 anos, residentes em quatro cidades diferentes localizadas no Sudeste (n = 1) e Sul (n = 3) do Brasil, foram realizadas coletas de dados entre 2004 e 2012. As maiorias dos estudos tiveram desenho transversal e os achados de todas as pesquisas foram publicados em revistas internacionais. A definição de “participação esportiva” não foi a mesma em todos os artigos. A prevalência geral de participação esportiva entre adolescentes foi de 58,1%, maior entre os meninos (65,9%) do que nas meninas (51,5%). A revisão sistemática identificou que a prevalência de participação esportiva entre adolescentes brasileiros é baixa e significativamente afetada por gênero.
Prevalência da participação esportiva entre adolescentes brasileiros: uma revisão sistemática
Keywords: Adolescent behavior; Child; Epidemiology; Sports; Comportamento do adolescente; Criança; Epidemiologia; Esportes